COMMUNITY STRUCTURE OF GROUPER FISH (Serranidae) LANDED IN PEUKAN BADA SUBDISTRICT, ACEH PROVINCE - Rika Astuti; . Yonvitner; M. Mukhlis Kamal (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
ABSTRACTInformation on important and economic grouper fish (Serranidae family) in Peukan Bada waters, Province of Aceh is very limited. This objecives of this research were to determine spatial and temporal variabilities in species composition and community structure of grouper landed in Peukan Bada, Aceh Besar District. The research was conducted using survey method during February to June 2015 on three fish landing sites i.e., Ujong Pancu, Lamtengoh, and Lamteh. The groupers were caught by using handline. The landed fishes were therefore counted and identified up to species level. The data were also analyzed based on taxonomic information and individual number of each species, community structure using the diversity index (H’), eveness (E), and dominance (D). The results obtained 835 individual, 21 species of grouper belong to 4 genera (Aethaloperca, Cephalopholis, Epinephelus dan Variola). Based on species, Epinephelus fasciatus and Cephalopholis sonnerati were the most grouper fishes in the region. Based on community structure, diversity value (H’) in Lam-tengoh was higher than that in Ujong Pancu and Lamteh. Total grouper fish catches were not significantly different (P>0,05) among the three region. Meanwhile, total grouper fish cacthes were significantly different between seasons (p<0,05). The diversity species variation during five months of observation was affected by the differences in catches area, the condition of aquatic enviroment, and oceanographic condition.Keywords: Groupers, Peukan Bada, species composition, community structure